Accuracy of Ultrasonogram in Diagnosis of Acute Appendicitis (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Acute appendicitis is one of the most common causes of abdominal pain of adult patients referred to the emergency department. Despite its prevalence, the diagnosis of appendicitis can be elusive and fraught with pitfalls because of the absence of a pathognomonic sign or symptom and the poor predictive value of laboratory testing. So following the significant advances in accuracy, ultrasonography has become an important part of the modern work-up of acute appendicitis.Objective: To evaluate the role and accuracy of ultrasonography in the diagnosis of acute appendicitis. Materials and Methods: A total number of 110 cases (65 men and 45 women), with clinical suspicion of appendicitis, were subjected to abdominal ultrasonographic examination. All ultrasonographic positive cases and a few of ultrasonographic negative cases were subjected to operative intervention.The accuracy of ultrasonography in the diagnosis of appendicitis was compared with the clinical diagnosis, operative findings and histopathological examination reports. The statistical analysis was done by using SPSS10.Results: Among 110 cases, 77 cases were sonographically positive for appendicitis and 5 cases were appendicular masses. The cardinal signs were right lower abdominal tenderness, rebound tenderness and positive Rovsing’s sign. The specificity of Ultrasound was 74.28%, sensitivity 90.66%, positive predictive value 88.31%, negative predictive value 78.79% and accuracy was 85.45% in the diagnosis of acute appendicitis.Conclusion So far the cost reduction of treatment and negative laparotomies are concerned, the ultrasonography is still an useful tool in the diagnosis of appendicitis in spite of more recent investigations like CT abdomen and Laparoscopy.Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 33-37